The importance of the relationship between green tourism and eco-tourism An analytical study on the sustainability of tourism resources - Mohsin Mahdi Rebat,; Ahmed Naji Hussein Alabedi,; Ali Fadhil Albo yousif, (International Journal of Psychosocial Rehabilitation, 2020)
Attention to the environment has become a major place in our world because of the multiple activities of life, which have greatly affected the environment that surrounds us. And its various resources, which called on many advocates to preserve the resources and their high voices in the specialized international forums, and since tourism is an important sector whose activities affect the tourism environment, whether natural or constructive, and directly touches those resources Our study, "The Importance of the Relationship between Green Tourism and Environmental Tourism - An Analytical Study on the Sustainability of Tourism Resources" came in two parts , So the first part started by presenting the problem, importance, hypothesis, objectives, and method of research, and the study touched on the theoretical concepts and trends explained to the study by analyzing the relationship between green and environmental tourism and the sustainability of tourism resources. As for the second part, it includes the practical side of the study, then the results, recommendations, sources and references.